lingkungan keluarga Pengaruh Lingkungan Keluarga Terhadap Prestasi Belajar Siswa Setingkat Menengah Atas: The Influence of Family Environment on the Learning Achievement of Upper Secondary Student - Ahmad Muhammad Ramadhan; Edo, Moch Edo Septianto; Kholidah, Siti Kholidah Rodiyah (CV Edujavare Publishing, 2025)
This study analyzes the influence of the family environment on students' learning achievement at the senior secondary level, including senior high school, vocational high school and senior high school. The family environment is seen as an external factor that plays a significant role in shaping the character, motivation, learning attitude, and independence of students in undergoing the learning process at school. This study applies a literature study strategy by analyzing various scientific sources such as journals, articles, and previous research results according to the context. The results of the study show that a supportive family environment, characterized by parental attention, good parenting, a conducive home atmosphere, and adequate learning support tools at home, can clearly increase the desire to pursue knowledge, independence, and academic achievement of students. Conversely, a less conducive family environment, such as a lack of moral support, economic pressure, or a lack of interaction time between guardians and children, tends to hinder the improvement of students' knowledge transfer potential. This research emphasizes the importance of collaboration between families and schools to create an optimal learning climate, and underlines the need for more attention to the role of families in supporting students' academic success in the modern era.